The effects of food product types and affective states on consumers' decision making. Issue 10 (30th September 2014) - Lin, Hung-Chou
Abstract : Purpose: – The purpose of this paper is to explore the effects of food product types and affective states and on consumers' variety seeking (VS) tendency. Design/methodology/approach: – Two experiments are conducted in this paper to examine the influence of different food product types and the VS-mood state relationship. Findings: – The results are consistent with the author's hypotheses and indicate that happy people incorporate more VS when healthful and unfamiliar food products are offered, while sad people incorporate more VS when hedonic and familiar food products are offered. Practical implications: – Marketers of leading brands selling hedonic food products could cultivate positive emotions in their target consumers in order to prevent them from switching brands. Conversely, marketers of follower brands may find it appropriate to induce negative moods in their consumers to encourage brand switching. For those marketers who sell less hedonic, healthier food products, marketing strategies should be contrary to those for hedonic food products. In addition, marketers may conduct strategies to prevent consumers from feeling sad in the case of products with a low market profile and which are unfamiliar to their consumers. They could cultivate happy moods in consumers to encourage them to make more varied food product choices. Originality/value: – Prior research has focussed mainly on hedonic and familiar products when explaining VS behavior, but the present research has demonstrated the need to discuss different product types, such as healthful and unfamiliar products, in order to obtain a broader understanding of affective states on VS.